PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP SELF CONCEPT DITINJAU DARI KEMAMPUAN AWAL MATEMATIS - Akhmad Marium; Heni Pujiastuti; Abdul Fatah (UJMES (Uninus Journal of Mathematics Education and Science), 2019)
Learning using the Realistic Mathematics Education approach is a learning model using a teaching approach that starts from the things that are real for students in the learning process. The Realistic Mathematics Education (RME) approach in learning applied to class VII A SMP Negeri 3 Ciruas as a sample used as an experimental class has shown an increase in student attitudes in terms of their attitude is a self concept. Learning that is carried out both in class and outside the classroom will work if there are students who have high creativity, of course, in thinking. One of the supports for the creative mindset of students is the application of learning models that are used like the Realistic Mathematics Education (RME) approach which serves to Improve Self Concept in terms of Students' Early Mathematical Capabilities in Learning Activities.